Regulation of the Escherichia coli methylgalactoside transport system by gene mglD. - Robbins, A R (1975)
Constitutive activity of the methylgalactoside transport system of Escherichia coli K-12 is shown to result from mutation of a genetic locus distinct from the two previously described regulatory loci for this permease. Employing an autoradiographic procedure whereby constitutive and inducible cells can be differentiated, it is demonstrated that this locus, termed mglD, is 20% cotransducible with ptsF by bacteriophage P1. Selection for constitutive mutants among an inducible population yielded cells who mutations mapped in mglD. Cotransduction of mglD with mglB, minus C, and minus A, three genes required for activity of the methylgalactoside transport system, is 95, 88, and 81%, respectively. The results of recombination studies employing three and four factors indicate that the order of genes in this region is ptsF, mglD, B, C, A.